Pengaruh Atribut Perusahaan Terhadap Relevansi Laba dan Arus Kas - Novi Indriana Soepratikno; Jogiyanto Hartono (The Indonesian Journal of Accounting Research, 2013)
The purpose of this study is to test whether there are linear or non linear relationship between stock returns and accounting variables (earnings and cash flows) in Indonesia and how firm-specific attributes such as size, debt level and firm life-cycle influence the relative relevance of earnings and cash flows in explaining stock returns.The results support a linear relationship between stock returns and accounting variables.  They indicate that earnings change reveals more information for small firms and large firms.  With regards to cash flows, we find that they do not reveal additional information beyond that contained in earnings for small firms and also for large firms.The results based on debt level indicate that for high leverage firms and low leverage firms, earnings change is the most relevant accounting variable in explaining stock returns, while the cash flows reveal a greater incremental information beyond that contained in earnings for high leverage firms than for low leverage firms.The regression results based on firm life cycle indicate that the most relevant accounting variable for growth firms and mature firms is earnings change.  In addition, cash flows reveal a greater incremental information beyond that contained in earnings for growth firms than for mature firms.